2013
DOI: 10.1016/j.ecoenv.2012.12.025
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of 2,4-dichlorophenoxyacetic acid in the Amphibian Metamorphosis Assay and the Fish Short-Term Reproduction Assay

Abstract: 2,4-Dichlorophenoxyacetic acid (2,4-D) was evaluated in both the Amphibian Metamorphosis Assay (AMA) and the Fish Short Term Reproduction Assay (FSTRA). In the AMA, tadpoles were exposed to mean measured 2,4-D concentrations of 0 (water control), 0.273, 3.24, 38.0 and 113 mg acid equivalents (ae)/L for either seven or 21 days. In the FSTRA, fathead minnows were exposed to mean measured 2,4-D concentrations of 0 (water control), 0.245, 3.14, 34.0, and 96.5 mg ae/L for 21 days. The respective concentrations of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 23 publications
0
19
1
Order By: Relevance
“…USEPA (2005) stated that the maximum predicted concentration of 2,4-D in aquatic habitat is between 2000 and 4000µg/L, while the reported maximum concentration in freshwater aquatic ecosystem range from 0.015 to75µg/L (Coady et al, 2013). The estimated half life in the aquatic environment is between 2.5 and 3.2 days (Wilson and Arbruster, 2007) as it is easily degraded in the environment by microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…USEPA (2005) stated that the maximum predicted concentration of 2,4-D in aquatic habitat is between 2000 and 4000µg/L, while the reported maximum concentration in freshwater aquatic ecosystem range from 0.015 to75µg/L (Coady et al, 2013). The estimated half life in the aquatic environment is between 2.5 and 3.2 days (Wilson and Arbruster, 2007) as it is easily degraded in the environment by microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…The FSTRA Coady et al 2013) showed no findings likely to be associated with increased or decreased testosterone or estradiol. Secondary sex characteristics, fertility, gonadal somatic index (GSI), gonadal histopathology, and VTG levels were not affected in this study in males or females.…”
Section: Ecotoxicological Studiesmentioning
confidence: 97%
“…Specific data are provided for the quail study because this study was unpublished and it is the only relevant bird study identified. Further details on these studies may be found in Supplementary Appendix III and, for the frog and fish assays, in Coady et al 2013. Regulatory and published studies with Klimisch scores of 2 or higher that are relevant to evaluation of potential endocrine interactions are summarized in Supplementary Appendix III.…”
Section: Toxcastmentioning
confidence: 99%
See 2 more Smart Citations